Treating diabetes in the elderly: overcoming challenges - Strain, David (Henry Stewart Talks, 2020)
Diabetes as a growing problem, Predicted outcome when diabetes and frailty are associated, Accomplishing the assessment of frailty through short consultation, The complexity of treating frail older adults with diabetes, Predicting benefit of response by frailty when creating treatment targets – Determining HbA1c targets for older adults according to their frailty condition, Targeting via HbA1c (~7.5%) in fit older adults to improve longevity, Targeting via HbA1c (8%) in moderate frailty to reduce microvascular complications, Targeting via HbA1c (8.5%) in severe frailty to improve quality of life, Re-assessing interventions after three months due to dynamic nature of frailty